Habitação Colaborativa: ensaio num lote da Rua de Dom João IV na cidade do Porto - Cristiano Catanzaro Zan (2020)
The dissertation was developed from an extensive research on collective and alternative ways of living to its contemporaries. In a first part, the work traces an evolutionary line creating relationships and interconnections from the utopian socialists of the early 19th century to the first cohousing communities founded in the second half of the 20th century. As an example, they can be cited: New Lanark, Phalanstère, Familistère, Central kitchen buildings, Narkomfin, Garden-Cities, Hufeisensiedlung, Kibbutz, Berlin Wall, Oscar-Niemeyer-Haus, Unité D'Habitation, Conservatization of the post-war society, Suburbanization, Hippies, Demonstrations of 68, Freetown Christiania, Illegal squatings in Zurich, Saettedammen, Skraplanet, Stacken, Autonomes Jugendzentrum, Karthago, Dreieck, Kalkbreite, Zollhaus, and finally the city of Porto. In the chosen route, the themes and buildings listed above elucidated the evolutionary line of thought and social aspects of each of these initiatives and experiments, highlighting the architectural response to the social demand for community life and coexistence. Collaborative housing is one among the many lines and ramifications of the collective way of thinking, which provides community living based on the sharing of social spaces, goods, and mutual cooperation among people who choose this way of living as an alternative. In the end, a project-oriented essay is proposed with the objective of architecturally responding to a hypothetical occupation of a Oporto's bourgeois house, from the second half of the 19th century, by a collaborative housing community.